Chromosomal studies on five species of the genus Leptodactylus Fitzinger, 1826 (Amphibia, Anura) using differential staining - Silva, A. P.Z. [UNESP]; Haddad, C. F.B. [UNESP]; Kasahara, S. [UNESP] (My University, 2000)
Cytogenetic studies were carried out on five species of Leptodactylus, namely L. fuscus, L. notoaktites, L. labyrinthicus, L. ocellatus, and L. podicipinus, after standard staining, Ag-NOR and C-banding as well as BrdU incorporation for three of them. The species had 2n = 22 chromosomes and two basic karyotype patterns. Chromosome 8 was a marker bearing a secondary constriction. In all species, this secondary constriction corresponded to the Ag-NOR site. The species had centromeric C-bands in all chromosomes of the complement, but some interstitial or telomeric bands seemed to differentiate some karyotypes, either at the species or the population level. In L. ocellatus, the C-banding pattern confirmed the occurrence of a heteromorphic pericentric inversion in chromosome 8 in specimens from one of the populations. The BrdU incorporation technique showed no detectable difference in the replication patterns of the major bands in the chromosomes of L. notoaktites, L. labyrinthicus, and L. ocellatus.
Keywords: Amphibia; Banding techniques; Brdu replication bands; Chromosomes; Cytogenetics